Understanding Commuting Mode Selection: A Case Study of Trinity College Dublin - Alonso Valdivia, Leyre (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2025)
Over the last few decades, the increase of pollution levels and greenhouse gas emissions has been a reason for concern for governments, individuals, and the scientific community. With transportation being a major contributor to the problem, research has focused on the factors involved in Transport Mode Selection. This thesis focuses specifically on Commuting Transport Mode Selection. Commuting behaviour is largely different from other types of transport-related behaviours due to its specificity and stability. The regular, mostly compulsory nature of commuting heavily restricts the when, where, and how the behaviour happens. However, despite the agreed complexity of commuting, most research has followed a too-narrow approach. Research has presented a wide number of factors involved in transport mode selection in regards of commuting, yet it has failed to consider how the main factors affect the behaviour when studied together. The research conducted in this thesis aims to address this gap, while also widening the methodological approach used. For this, this research was based on two theoretical approaches, the Value-Belief-Norm Theory and the Campbell Paradigm, under which values, attitudes, beliefs, and personal and social norms were studied. Additionally, this research also included a wide range of socio-demographic and contextual factors, such as accessibility. This study used a combined quantitative-qualitative methodology. The sample were staff and students at Trinity College Dublin. Firstly, a quantitative, questionnaire-based methodology was employed. This aimed to study a wide number of factors with the goal of identifying those that had the stronger impact on mode selection. For this, a repeated measures approach was employed, gathering data at two times. The sample size for Time 1 was of 1029 participants, and for Time 2 consisted of 241 participants. The results found, informed the factors involved in the second study. This second study followed an interview-based qualitative approach with the goal of obtaining a more in-depth understanding of how the different factors influenced mode selection. The sample consisted of 20 participants recruited from among those that had taken part in the survey study. The results found in this research speak of commuting transport mode selection as hierarchy, in which the different factors influence the decision at different stages. This challenges previous research in which the factors either had an influence in mode selection or they did not. Instead, these results propose the idea that the factors do have an impact in mode selection, but at different points in the decision-making process. This research proposed a 3-stage hierarchy of how the different factors are involved in commuting transport mode selection. This research presents a new way of approaching the study of commuting transport mode selection and opens the doors for a new pathway for interventions related to mode selection.
APPROVED
Keywords: VBN; Campbell Paradigm; Transport Mode Selection; Commuting; COVID